R2T2: Robotics to integrate educational efforts in South Africa and Europe. (30th September 2016) - Mondada, Francesco; Bonnet, Evgeniia; Davrajh, Shaniel; Johal, Wafa; Stopforth, Riaan
This paper presents the first cross-continental collaborative robotic event based around education. It was entitled R2T2 and it involved more than 100 children from Europe and Africa. Based on remote programming, video streaming feedback, and a scenario of collaborative space rescue, R2T2 focused on pedagogical elements that are fundamentally different than those characterizing classic robotic competitions. The value of these educational actions is shown through the results of a survey conducted among the participants; the working methodologies by the African students were significantly enhanced and there was a broad inclusion in general, despite the fact that some gender issues lingered. This paper's contribution is to demonstrate an approach to implementing a north-south collaboration to get school students excited about robotics and the problem-solving skills required in engineering.